EFEK PEMBERLAKUAN UU NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA TERHADAP PEGAWAI HONORER - Moh. Rosyid (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Interest of become civil servants (PNS) are always great, especially for young scholars living in the village. This is caused by the embarrassment of living in the village due to limited access to economic resources. Thus becoming civil servant comes across their mind and they are competing for the seats. For those who are not able to compete, they are willing to become a temporary employee in the office. The numbers of temporary employee endanger national stability because the process of recruitment neglects the ability of local cash or units of work in salary. This was addressed by the government with the enactment of Law No. 5 of 2014 on Civil Administrative State (ASN). The bill states that the appointment of civil servants should be rely on future service work.Keywords: servant, temporary employee, and dynamics